Chakshudana or Opening the Eyes Seeing South Asian Art Anew - Ghosh, Pika; Sohoni, Pushkar (Taylor & Francis, 2023)
Art, Art History, temple art, South Asian Art, South Asian architecture, temple architecture, Michael W. Meister, visual and material culture